Improving the Mechanisms of Trainer-Athlete Dyad Relations in Sports Schools - Ermatov Sardor Abdurakhmon Ogli (Genius Journals, 2023)
Due to the increasing influence at present, despite the dynamics of intimate relationships, the importance of understanding the mechanisms for the formation of interpersonal relationships increases, in the analysis of which specific sociological and socio-psychological aspects prevail. The relationship between the coach and the athlete is increasingly attracting the attention of specialists, primarily due to the clear influence of their characteristics, which are formed in each case, on the effectiveness of education and training, on the formation of the personality of the audience, and often on the results of direct competitions.
Keywords: attitude; component; training; sports